Vegetation Development in a Degraded Area under Bamboo Based Agro-Forestry System - Behari, Bipin; Agarwal, Rashmi; Singh, A. K.; Banerjee, S. K. (Indian Forester, 2000)
The phyto-sociological aspects of the highly degraded basaltic tract of Jabalpur, Madhya Pradesh were studied to assess the impact of Agro-forestry models of Bamboo cultivation with the short term agricultural crops on the restoration of ecology. The ground flora was recorded at four Agro-forestry sites with a control in October, 1996 and 1997. The results obtained from the study revealed that there was considerable increase in number of species, diversity index and species richness as compared to control in both the years. The increase was more conspicuous in the second year. Poaceae was found to be the dominant family on all the sites. Reduction in number of species at the control site has been attributed to the heavy biotic interference. The ecological parameters studied revealed that the degraded agricultural lands can be ecological restored and improved fast through the development of Bamboo based Agro-forestry models.